M-Commerce: A Revolution in E-Business (International Journal of Engineering and Computer Science, 2018)
With the advancement of traditional business to electronic business and then electronic business to mobile commerce, the technology changed rapidly. Mobile-Commerce (M- Commerce) has come into existence with the advancement of wireless technology which increases the number of mobile device user and gives a rapid development of e-commerce using these device. M-Commerce is a special type of E-Commerce where all transaction has to be done by mobile phones. Earlier mobile devices are used only for phone calls and SMS but nowadays mobile devices are part of our daily life for doing different type of transaction like mobile banking, mobile ticketing, mobile money transfer etc. More and more users are connected with Smartphone and access their mobile services by installation of applications.